Hubungan Antara Persepsi Terhadap Iklim Sekolah Dan Konsep Diri Dengan Kemandirian Belajar - Anggraini, Catur, Taufik, S.Psi., M.Si., Ph.D (2017)
Corelation Between Perception Toward School Environment And Self Concept With Learning Independence The aims of this research are: 1) to know the correlation between perception toward school environment and self-concept by learning independence; 2) to know the influence or effective contribution of perception toward school environment and self-concept in learning independence. The subject of this research is the twelfth grade (XII) students of SMA N 1 Purwantoro. The methods of the sample uses cluster random technique by choose 70 students class of XII A and XII C. The technique of analyze the data uses regression of two predictors. The result of this research shows that: there is significant positive correlation between perception toward school environment and self-concept with learning independence. The condition of perception toward school environment on subject of research was high, self-concept on subject of research was high, and learning independence on subject of the research was also high. The effective contribution of perception toward school environment toward learning independence is 29%. The effective contribution variable of self-concept toward learning independence is 16%. The amount of effective contribution toward school environment and self-concept toward learning independence is 45%.